Aglaonema modestum Chinese Evergreen - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS)
This document presents a comprehensive analysis of theChinese evergreen (Aglaonema modestum), a perennial plant favored for its ornamental value and adaptability to low-light conditions. Native to tropical and subtropical regions of Asia, this species is ideal for indoor cultivation, thriving in USDA hardiness zones 10B to 11. The study highlights the plant’s resilience to shade and its preference for moist, well-drained soils, with an emphasis on maintaining temperatures above 45°F to preserve its vibrant foliage. The article further explores the plant’s moderate resistance to common pests and its non-invasive nature, making it a suitable candidate for both container gardening and mass planting. Original publication date October 1999.